Philisophy And Implementation of Ijarah Contracts In Islamic Banking Practices In Indonesia - Havis Aravik; Aris Munandar; Hetti Nubila (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2026)
The ijarah contract is one of the main instruments in the Islamic banking system, functioning as a financing mechanism based on the utilization of assets or services without involving elements of usury (riba). This contract has a strong normative basis in Islamic jurisprudence (fiqh muamalah) and plays a crucial role in supporting the financial performance and operational stability of Islamic banks. However, the implementation of the ijarah contract in Indonesia still faces various challenges, including differences in interpretation between classical fiqh concepts and modern banking operational practices, variations in implementation among Islamic financial institutions, and limited customer understanding of the contract's substance. Furthermore, most previous studies tend to emphasize quantitative and financial aspects, thus underexploring the philosophical dimensions, ethical values, and substantive objectives of sharia inherent in the ijarah contract. This study aims to analyze the philosophy, social function, and implementation of the ijarah contract in Islamic banking practices in Indonesia, emphasizing the alignment between normative concepts and operational realities. The method used is qualitative research with a descriptive-analytical approach through literature review, documentation, limited observation, and in-depth interviews. The research results show that the ijarah contract is regulatory and complies with the DSN-MUI fatwa and OJK regulations and provides significant economic and social contributions. However, gaps remain in philosophical understanding and consistent implementation, particularly in the practice of ijarah muntahiyah bit tamlik (IMBT). Therefore, strengthening the values of maqasid sharia and harmonizing practices are necessary.